Corrigendum: Analysis of Eco-Enzyme Potential to Reduce BOD, COD, Oil and Grease Concentrations in Raw Water for Treated Water in Karawang: A Laboratory Experiment - Gina Lova Sari; Wilma Nurrul Adzillah; Kania Ratnawati; Devita Fitria Alam Sari; Saidah Saidah (Poltekkes Kemenkes Surabaya, 2026)
This corrigendum is issued to correct several editorial and typographical errors in the article entitled